THE STUDY OF THE NARRATOR IN HERMAN RN'S SHORT STORIES - Wildan Wildan; Yusri Yusuf; Denni Iskandar (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to explore and strengthen the concept of narratology as one of the theories of contemporary literature. The study focuses on three aspects, namely the various forms of the narrator, the dominant type of greeting, and the unique characteristics of the work. The object of this study is 38 short stories by Herman RN which were published in various media and anthologies from 2005 to 2020. This research uses an objective approach, with qualitative-descriptive methods and content analysis techniques. The research findings are (1) the form of the narrator in the Herman RN’s short stories consisting of the first-person narrator (55.26%) and the third-person narrator (44.74%); (2) the dominant type of greeting used by the narrator who tells the story by referring to himself as "Aku = I" or "saya = I" (or other synonyms) or by referring to the object being told, such as ‘dia = he, -nya = his, (or the name of the character); and (3) the short stories have not shown certain characteristics that have become a trend in the use of these narrators. The research concludes that the storytelling system of Herman RN's short stories is simple, easy to understand, and consistent with one choice.